Green supply chain management and company performance: a case of logistics companies in Kemaman / Nur Zarith Sofea Mohamed - Mohamed, Nur Zarith Sofea (Faculty of Business and Management, 2013)
The purpose of this study is to indicate the impact of green supply chain practice on company’s performance. There are five independent variables used in this study which are internal environmental management, green purchasing, cooperation with customers, eco-design and warehouse and green building. The objective of this study is to examine the relationship between all independent variables with company’s environmental, economic and operational performance, to identify the factors that influence company’s environmental, economic and operational performance the most and to evaluate whether there are differences in the average environmental, economic and operational performance of companies based on the type of environmental management system that they adopt. For this study, the researcher has collected questionnaires from logistics companies in Kemaman, Terengganu. In order to collect the questionnaires, researcher used convenience sampling technique where the researcher randomly picks the logistics companies in Kemaman including in Kemaman Supply Base (KSB) area as her respondents. Besides that, for testing the objectives of this study, researcher was used three method of SPSS data analysis which is Pearson Correlation Analysis, Multiple Regression Analysis and One-way ANOVA. From the findings, the result for first objectives shows there is a significant relationship between independent variables and dependent variables. For second objective, the result shows eco-design is the factor that influences company’s performance the most. For last objectives, is shows environmental management system only affected environmental performance. However, in order to complete this study, there are some limitations faced by researcher. The first limitation is in term of gaining accurate and correct information and second limitation is in term of sample size. For this study, there recommendation was given by researcher which is adding others variables, give more attention to eco design and have effective internal environmental management.